Mathematical basis of formatting digital models of relief - Radenko I. Višnjić (Vojnotehnički Glasnik, 2000)
This paper deals with a mathematical basis used for formatting the Digital Models of Relief (DMR) of the Earth's physical land surface. The theoretical and mathematical basis is described and mathematical expressions for approximation of the lines and surface elements in formatting relief's space structural features are given. These expressions are significant for the selection of appropriate solutions while using computer support in the DMR making procedure. The selections depend on their application and a required accuracy.